Pendekatan Fisik dan Spiritual dalam Mengatasi Kantuk saat Menghafal Al-Qur'an di Pagi Hari - Melvin Irawansyah (GHIROH, 2025)
This article discusses ways to overcome drowsiness, which often becomes a major obstacle in the process of memorizing the Qur'an, especially in the morning. It examines the effectiveness of physical and spiritual approaches in combating drowsiness during Qur'an memorization. The study was conducted through literature review and observations of several students at the Al Ihsan Bintan Islamic boarding school. The results show that a combination of physical strategies such as movement, walking, deep breathing, and maintaining hydration, along with spiritual approaches like performing ablution (wudhu) and strengthening intention, significantly helps reduce drowsiness levels and improve the quality of memorization. The conclusion of this study recommends integrating both approaches for optimal results in the Qur'an memorization process.